2020
DOI: 10.1080/07399332.2020.1830096
|View full text |Cite
|
Sign up to set email alerts
|

Polish maternity services in times of crisis: in search of quality care for pregnant women and their babies

Abstract: The current COVID-19 pandemic put a burden on healthcare services around the globe and impacted many areas of care delivery, including maternity services. Prioritizing ringfenced community care to keep women away from hospitals may be the best strategic response to ensure pregnant and laboring women receive optimal care. By analyzing the structure of maternity services in Poland and their response to the current crisis, we show that while the available model allows to provide large share of prenatal services o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…During such meetings or classes, it is absolutely essential to follow the guidelines and adhere to all necessary safety precautions for limiting the spread of COVID-19 [6,8,10]. The aim of these recommendations was and still is to limit the possibility of infection with the SARS-CoV-2 virus for both patients and the health care professionals who care for them [2][3][4][5][6][7][8][9][10].…”
Section: O N L I Nmentioning
confidence: 99%
See 3 more Smart Citations
“…During such meetings or classes, it is absolutely essential to follow the guidelines and adhere to all necessary safety precautions for limiting the spread of COVID-19 [6,8,10]. The aim of these recommendations was and still is to limit the possibility of infection with the SARS-CoV-2 virus for both patients and the health care professionals who care for them [2][3][4][5][6][7][8][9][10].…”
Section: O N L I Nmentioning
confidence: 99%
“…The implementation of sudden changes in perinatal care in conditions of uncertainty and threats to occupational safety has increased the sense of anxiety among health care workers, including midwives [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It has also intensified the need to investigate the determinants of these problems [18][19][20].…”
Section: O N L I Nmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Netherlands, partners Covid-19 symptoms could accompany woman if they donned respiratory masks and kept their distance [18]. In Poland, Wegrzynowska et al reported that partners with negative test results could accompany women, but the tests were expensive and di cult to procure [49].…”
Section: E Exclusion Of Accompanying Personsmentioning
confidence: 99%